2010
DOI: 10.1007/s00134-009-1748-1
|View full text |Cite
|
Sign up to set email alerts
|

Prone ventilation reduces mortality in patients with acute respiratory failure and severe hypoxemia: systematic review and meta-analysis

Abstract: Prone ventilation reduces mortality in patients with severe hypoxemia. Given associated risks, this approach should not be routine in all patients with AHRF, but may be considered for severely hypoxemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
330
3
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(361 citation statements)
references
References 67 publications
11
330
3
17
Order By: Relevance
“…It must also be emphasized that the most recent studies reported mortality rates for patients with the most severe forms of ARDS, defined as hypoxemia or hypercapnia refractory to initial management and treated conventionally, exceeding 60% [1][2][3]. The results of the first randomized trial were disappointing, but it should be noted that it took place many years ago, when the technology was in its infancy.…”
Section: Why a New Trial Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…It must also be emphasized that the most recent studies reported mortality rates for patients with the most severe forms of ARDS, defined as hypoxemia or hypercapnia refractory to initial management and treated conventionally, exceeding 60% [1][2][3]. The results of the first randomized trial were disappointing, but it should be noted that it took place many years ago, when the technology was in its infancy.…”
Section: Why a New Trial Now?mentioning
confidence: 99%
“…The most severe forms of the disease, of which hypoxemia resulting from pulmonary involvement is the most profound, have an even worse prognosis, with mortality exceeding 60% [2,3], despite recourse to exceptional adjunctive therapies, such as inhaled NO [4], recruitment maneuvers [5], or prone positioning [6].…”
Section: Introductionmentioning
confidence: 99%
“…Severely ill patients, those experiencing improved CO 2 exchange, and those ventilated with large tidal volumes appear more likely to benefit than other members of the general cohort [5]. A superb meta-analysis of pooled data appears in this issue, focusing on those relative few with the worst oxygen exchange [8]. This analysis shows convincingly that, while proning cannot be recommended for all patients with acute lung injury, it does hold therapeutic value for some.…”
mentioning
confidence: 97%
“…The novel contribution of the report by Sud et al [8], which included studies regardless of proning duration and timing, is that the meta-analysis pools the collective published experience with patients with uncommonly severe disease and thereby helps define the subpopulation likely to benefit from an inconsistently life-saving intervention. Even severe hypoxemia, however, may itself be too inclusive a category to identify those most amenable to PP.…”
mentioning
confidence: 99%
See 1 more Smart Citation